The Influence of organizational support and employee work engagement on employee performance at PT Everbright - Sugiarto Sugiarto; Mohd. Nawi Purba; Ara Auza (Institute of Computer Science (IOCS), 2024)
This study, conducted from May 2023 to January 2024 at PT Everbright, examined the impact of organizational support and employee work engagement on employee performance. Using a census method, all 165 employees were included as research subjects. Multiple linear regression analysis revealed that both organizational support and employee work engagement significantly and positively influenced employee performance. The findings indicated that organizational support (tcount = 3.744, p = 0.000) and employee work engagement (tcount = 6.633, p = 0.000) had significant effects on performance. Simultaneously, these variables had a positive and significant impact on performance (Fcount = 65.485, p = 0.000). The adjusted R Square value was 0.440, suggesting that 44.0% of employee performance could be explained by organizational support and employee work engagement, while 56.0% was influenced by other unexamined variables such as work environment and rewards